MATI SAJRONING NGAURIP SEBUAH ANALISIS HERMENEUTIS-FENOMENOLOGIS TENTANG MAKNA PENDERITAAN DALAM SERAT KALATIDA KARYA RADEN NGABEHI RONGGOWARSITA - Waskito, Ardian Agil (Jurnal Psikologi, 2010)
Ranggawarsita (1802-1873), with his Serat Kalatida, attempt to analyze the condition which he considers his era full of doubt so devastated humanity. Ranggawarsita has been suggested the insanity period and his views on humanism through these serat, before the emergence of similar views in Europe. What is described in the Serat Kalatida with connotative language is considered to be still relevant today, because today's conditions are resemble with the era who Ranggawarsita described, so the serat was kept under review by various disciplines. Nevertheless, researchers are still very few studies assessing the work of this Ranggawarsita from the stand point of psychology. The purpose of this study was to examine and know the meaning of suffering as described in the Serat Kalatida. Researchers hope that by knowing the meaning of this suffering, it will be able to help many individuals to be able to reach the meaning of suffering. Serat Kalatida fiber is connotative and rhymes that require interpretation effort to it, then the hermeneutic method was chosen to be used in this study. Researchers in this study using a hermeneutical-phenomenological study presented by Heidegger, basing on the involvement of the text as subject, author and researcher himself, done by continuing to maintain these components to be in the relevant context. Based on the analysis, it can be explained that the existence of human beings to be able to reach most essential meaning of his suffering on the journey through the three stages of human existence. The first stage is kalatida, which is the root of suffering and the beginning of human personal spirituality dissapear, to later become the mode era, when the socially integrated in the flow of the flooded kalatida in the ati world, until then seep back into the ati in human personal level. The second phase is marked by a leap in human aesthetics in the kalatida to be the human darsana as ethical personality that is able to embrace the meaning of suffering in an ethical, with a through road pinikir sayekti, eling and waspada, niteni, and always doing kaelokan. Peak phase of this existential search is in mati sajroning ngaurip, where a mystical man who has been able to purify his tyas, and became a great man in santosa, so the individuals will lead bond (kawula) with the universal reality of the Divine (Gusti) in suksma, or is familiarly known as the manunggaling kawula gusti. The results of this study is the simulative discourse to psychology study based on local wisdom, especially Java, more broadly, however, because human beings as part of its cultural narratives can only be understood in its cultural relativity. With the understanding of cultural values as part of the internal psyche, the study toward Serat Kalatida is expected to be an alternative in understanding the human mind through the East, especially the way of Javanese people thinking.Keywords: the meaning of suffering, Serat Kalatida, hermeneutical-phenomenological, kalatida, mati sajroning ngaurip.Permalink :